PERAN DAN KEBIJAKAN OTONOMI DAERAH PEMERINTAH KALIMANTAN TIMUR DALAM PEMERATAAN AKSES PENDIDIKAN: ANALISIS HUKUM ADMINISTRASI NEGARA - Angga Galucci; Irwanto; Muhlis; Muhammad Aulia Rahman; Andry Rachmadani; Siti Hardyanti (STKIP Subang, 2026)
Regional autonomy as regulated in Law Number 23 of 2014 concerning Regional Government gives regional governments broad authority in administering educational affairs as a basic service. In East Kalimantan, geographic challenges, disparities between regions, and the distribution of educational resources demand adaptive and responsive policies. This research aims to analyze the role and policies of the East Kalimantan Regional Government in equalizing access to education through the perspective of State Administrative Law, by examining aspects of authority, discretion, general principles of good governance (AUPB), as well as monitoring and accountability mechanisms. The research method used is normative juridical with a statutory and conceptual approach. Data was obtained through literature study of regulations, regional policies, and educational planning documents. The analysis was carried out qualitatively to assess the suitability of regional policies with the principles of legality, effectiveness and administrative justice. The research results show that local governments have a strategic role in planning, budgeting and supervising secondary education services, including the construction of infrastructure, distribution of teachers and the provision of educational assistance. However, policy implementation still faces coordination obstacles, budget limitations, and disparities in remote areas. Therefore, it is necessary to strengthen governance based on transparency, public participation and continuous evaluation in order to realize equitable and sustainable access to education.